2018
DOI: 10.1002/mnfr.201800142
|View full text |Cite
|
Sign up to set email alerts
|

Yerba Mate Stimulates Mitochondrial Biogenesis and Thermogenesis in High‐Fat‐Diet‐Induced Obese Mice

Abstract: YM stimulates mitochondriogenesis and Ucp expression, leading to an increase in the spare respiratory capacity and energy dissipation. These effects may help to better understand the potential use of YM for obesity treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 40 publications
1
7
0
1
Order By: Relevance
“…With the progress of pregnancy and rapid fetal growth, placental mitochondrial respiratory chain enzyme activity and ROS production are significantly increased . It has been demonstrated that SIRT1 is an important regulator of mitochondrial biogenesis and fatty acid oxidation, which interacts with PGC1α in various tissues and cells . In our study, it was observed that placental SIRT1 deficiency significantly decreased PGC1α mRNA and protein level.…”
Section: Discussionsupporting
confidence: 49%
“…With the progress of pregnancy and rapid fetal growth, placental mitochondrial respiratory chain enzyme activity and ROS production are significantly increased . It has been demonstrated that SIRT1 is an important regulator of mitochondrial biogenesis and fatty acid oxidation, which interacts with PGC1α in various tissues and cells . In our study, it was observed that placental SIRT1 deficiency significantly decreased PGC1α mRNA and protein level.…”
Section: Discussionsupporting
confidence: 49%
“…Recently, Nrf1 was proposed in thermogenic fat cells as a metabolic guardian, avoiding tissue stress and inflammation independently of BAT differentiation, mass or expandability [34]. In addition, in a previous study we revealed that Ilex paraguariensis , rich in phenolic compounds, increased mitochondriogenesis and energy dissipation in brown adipose tissue and skeletal muscle, which explained the mass change of these oxidative tissues [35]. However, taking into account the lack of change in brown adipose tissue and gastrocnemius weights, and even more, in white adipose weights, it seems that under our experimental conditions, there was no sharp EE modification.…”
Section: Discussionmentioning
confidence: 93%
“…Notably, the stated impacts had close bounded to bodyweight decline. Hence, yerba mate could relatively hinder diet-related obesity through escalating ATP consumption and induction of the biogenesis of mitochondria by AMPK/ SIRT1/PGC-1α-mediated cascade [94]. The green tea's efficacy on the biogenesis of mitochondria was investigated in vivo.…”
Section: Amla C2c12 Myotubesmentioning
confidence: 99%